Probabilistic Characteristics of Subprocesses in a Glow Discharge - I. M. Pastukh; G. N. Sokolova (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
As a result of analyzing experimental data, analytical expressions were developed for calculating the probabilistic characteristics of the most tangible subprocesses during nitriding in a glow discharge.